REPUTASI PENJAMIN EMISI SAHAM, REPUTASI AUDITOR DAN TINGKAT UNDERPRICING PADA PENAWARAN PERDANA DI BURSA EFEK JAKARTA - KHOMSIYAH (Jurnal Bisnis dan Akuntansi, 2005)
The purpose of this study is to test the relationship between auditors’ and underwriter’s reputation, abd underpricing. Previous studies found that initial public offering are underpriced. This study expected that the reputation of underwriters and auditors are negatively associated with underpricing. For underwriters and auditors are negatively associated with underpricing. For underwriters’ reputation proxy, we used market share which developed by Megginson and Weiss (1991) and auditors’ reputation proxy, we use auditor industry specialization. Based on the sample of 48 IPO firms listing in Jakarta Stock Exchange (JSX) during the period of 1998-2001, the result show that underwriters’ reputation and auditors’ reputation significantly associated with under pricing.